Desain Pemasangan Sistem Pembumian pada Gardu Induk Baru di Gardu Induk Kota Cane 1 x 30MVA Aceh Tenggara - Mashadi Mashadi; Olnes Yosefa Hutajulu; Kinanti Wijaya (Universitas Negeri Medan, 2023)
ABSTRACT The presence of reliable and continuous electrical energy is very important to support modern human life, therefore its necessary to build a transmission network that connect to each other between substations. One of the important components to maintain the availability of reliable electric power in addition to the electric power protection system is the grounding system at the substation. The grounding system is useful for minimizing electric power disturbances due to overvoltage originating from the operation of existing equipment in the substation system as well as due to other factors external is a lightning impulse. In this paper, we will describe how to design and install a grounding system in substations. The type of installation of the grounding system selected is the mesh or grid method. The making of this grounding system refers to the work plan and working contract conditions, formulas commonly use in electric power engineering theory, the applicable rules and regulation of electric power system. The most important standards and variables in this design are the type and resistivity of ground resistance, step voltage, touch voltage and the length of conductor used. The result of this design after working for one month in the new substation area and measured using an Earth tester showed good result of ≤ 0.19 ohm as required by the owner is 0.3 ohm. The result of this measurement mean that the result of the grounding system design has been successfully implemented is 0.19< 0.3 ohm.